2019
DOI: 10.1016/j.tranon.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Cysteine-Rich Protein 61 and Trefoil Factor 3 as Diagnostic Biomarkers for Colorectal Cancer

Abstract: Since a fecal occult blood test for colorectal cancer (CRC) does not offer sufficient diagnostic power for CRC, novel non-invasive biomarkers are hopeful for CRC screening. We conducted the current study to discover non-invasive urinary biomarkers for diagnosing CRC. Among urine samples from 258 patients (CRC, n = 148; healthy controls, n = 110), a cohort of 176 patients composed of 88 patients with GC and 88 healthy controls was selected after age- and sex-matching using propensity score. This cohort was then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Moreover, KNG1 was expressed at low levels in glioma cells (21) and renal cell carcinoma tissue (22). By contrast, increased KNG1 levels have been reported in the serum of patients with hepatocellular carcinoma (23), gastric carcinoma (24) and colorectal cancer (5). IHC staining revealed KNG1 expression to be significantly higher in colorectal cancer and advanced colorectal adenoma tissues than that in normal mucosa (25).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, KNG1 was expressed at low levels in glioma cells (21) and renal cell carcinoma tissue (22). By contrast, increased KNG1 levels have been reported in the serum of patients with hepatocellular carcinoma (23), gastric carcinoma (24) and colorectal cancer (5). IHC staining revealed KNG1 expression to be significantly higher in colorectal cancer and advanced colorectal adenoma tissues than that in normal mucosa (25).…”
Section: Discussionmentioning
confidence: 97%
“…Such biomarkers have been sought as a means of facilitating LUSC diagnosis and monitoring, since their detection is easier than a more invasive biopsy procedure and allow rapid screening. Minimally invasive tumor biomarkers that are readily accessible in biofluids such as plasma, urine and bronchoalveolar lavage fluid (BALF) would thus offer a means of easily and effectively differentiating between patients with cancer and those with benign disease (4)(5)(6). Urine markers can be detected without exposing individuals to any risk, and urine is highly amenable to large-scale screening efforts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNA (miRNA), which is a class of small noncoding RNAs comprising approximately [18][19][20][21][22][23][24][25] nucleotides, can regulate gene expression by binding to the 3′-UTR of target mRNAs post-transcriptionally, leading to translational inhibition, or promotion of RNA degradation (7). Dysregulation of miRNAs is reportedly involved in EC tumorigenesis and progression (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…However, no urinary biomarkers have been clinically applied to malignant cases. We have been exploring for urinary biomarkers for a long time and found that urinary protein biomarkers are useful for gastric cancer (15)(16)(17) and colorectal cancer (18). Moreover, we recently established a urinary miRNA biomarker panel using miR-6807-5p and miR-6856-5p; this panel can early detect gastric cancer (19).…”
Section: Introductionmentioning
confidence: 99%